Menentukan Keuntungan Maksimal dengan Menggunakan Program Linier Metode Simpleks pada Produksi Roti Isi Cokelat Keju dan Cokelat Kacang - Palahudin Palahudin; Hilda Sapitri; Nurul Aulia Fitriani; Mefi Septinis Zega; Ramadhani Ramadhani; Muhamad Ikbal Fadilla (Universitas 45 Surabaya, 2025)
This research aims to optimize profits in the production of chocolate-filled bread at Sasari Bakery using linear programming and the simplex method. This study is motivated by the need to improve operational efficiency and maximize profits in the context of production limited by resources. The simplex method is used to find the optimal solution regarding the quantity of bread that can be produced to maximize profits. The results of this study indicate that with the application of linear programming and the simplex method, Sasari Bakery can achieve a maximum profit (Zmax) of Rp. 82,500 per day, from a combination of profits from 3 pieces of chocolate nut bread (X1) and 10 pieces of chocolate cheese bread. (X2). Overall, this research makes a significant contribution to integrating mathematical optimization techniques in the small and medium-sized bakery industry (IKM), opening opportunities to improve efficiency, reduce waste, and maximize profits with limited resources.